Penggunaan Bahasa Indonesia dalam Ceramah Ustadzah Halimah Alaydrus - Shalma Putri Sulaeman; Agnitsani Shofia Afipah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The presence of Indonesian language in religious talks serves a significant purpose as an effective tool for communicating Islamic teachings. This research centers on how Ustadzah Halimah Alaydrus employs Indonesian in her sermons, noted for their respectful, clear, and pertinent presentation to listeners. The foundation of this investigation lies in recognizing the value of language analysis as a method of outreach that can engage diverse segments of the community. The inquiry focuses on how Ustadzah Halimah adeptly uses Indonesian to effectively communicate religious ideas in a precise manner. The research employs a descriptive qualitative method using a case study design. Data collection included reviewing recordings of lectures that were widely shared, conducting linguistic analyses, and performing supplementary interviews with audience members to gauge their reception of the language used. The findings indicate that Ustadzah Halimah incorporates straightforward yet impactful Indonesian words, modifies her tone between gentle and assertive, and weaves in inspiring stories relevant to daily experiences. This technique has proven successful in establishing a deep emotional link with the audience, enhancing their comprehension and acceptance of the conveyed messages. The study recommends that preachers receive training to refine their language abilities and implement these skills in their teachings. Within the academic field, this research adds to the body of knowledge in pragmatic linguistics and preaching communication, particularly in analyzing how language can serve as a persuasive tool that positively affects listeners. Therefore, the effective use of proper Indonesian should be further leveraged as a strategic approach to preaching in contemporary society.